2010
DOI: 10.1113/jphysiol.2010.187088
|View full text |Cite
|
Sign up to set email alerts
|

Development of light response and GABAergic excitation‐to‐inhibition switch in zebrafish retinal ganglion cells

Abstract: The zebrafish retina has been an important model for studying morphological development of neural circuits in vivo. However, its functional development is not yet well understood. To investigate the functional development of zebrafish retina, we developed an in vivo patch-clamp whole-cell recording technique in intact zebrafish larvae. We first examined the developmental profile of light-evoked responses (LERs) in retinal ganglion cells (RGCs) from 2 to 9 days post-fertilization (dpf). Unstable LERs were first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 59 publications
3
79
0
1
Order By: Relevance
“…Inhibition in the retina matures after the bulk of retinotopic refinement of retinocollicular projections is complete and retinocollicular glutamatergic synapses are strengthening (51). As inhibition plays a critical role in the formation of receptive fields, we suggest that the maturation of inhibition in the retina is completed in time for eye-opening and the onset of normal visual experience (24).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Inhibition in the retina matures after the bulk of retinotopic refinement of retinocollicular projections is complete and retinocollicular glutamatergic synapses are strengthening (51). As inhibition plays a critical role in the formation of receptive fields, we suggest that the maturation of inhibition in the retina is completed in time for eye-opening and the onset of normal visual experience (24).…”
Section: Discussionmentioning
confidence: 96%
“…In vivo recordings in zebrafish demonstrate that the timing of the GABA switch is critical for the timing of the development of light responses (24) and therefore might be linked to the onset of visual experience. Chronic blockade of GABA A receptors (GABA A Rs) in turtle retina prevents the normal maturation of spontaneous firing patterns termed retinal waves and the maturation of adult-like chloride gradients, implicating early GABA signaling in the normal maturation of inhibitory circuits in retina (15).…”
mentioning
confidence: 99%
“…In favour of a depolarizing GABA action in nonmammalian species in vivo, iontophoretic application of GABA or glycine was found to evoke somatic Ca 2 þ transients (CaTs) in spinal neurons of zebrafish larvae 34 . In addition, gramicidinperforated patch recordings showed that GABA depolarizes zebrafish retinal ganglion cells at an early developmental stage 35 . At present, only limited information is available on the intact mammalian brain.…”
mentioning
confidence: 99%
“…So gelang Zhang und Kollegen mittels Perforated-patch-clamp-Ableitungen der Nachweis einer depolarisierenden GABA-Wirkung in retinalen Ganglienzellen des Zebrafisches (Zhang et al, 2010). Hierbei zeigte sich ein Wechsel von de-zu hyperpolarisierender GABA-Wirkung zwischen Tag 2 und 3 nach Fertilisation, welcher zeitlich mit der Ausbildung sensorisch-evozierter PSC überlappte.…”
Section: Messungen In In-vitro-modellenunclassified